BACTERIAL VAGINOSIS ASSOCIATED WITH THE ABNORMAL BODY MASS INDEX - Icha Nur Oktaria; Juniastuti Juniastuti; Gatut Hardianto (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: Based on data in RSUD Dr. Soetomo Surabaya, showed that during the 2018 period, bacterial vaginosis was among the top 10 most diseases. One risk factor for bacterial vaginosis is still controversial is the body mass index. The purpose of this study was to determine the association between the incidence of bacterial vaginosis with body mass index in RSUD Dr. Soetomo. Method: The research data used secondary data. This research method was cross sectional with observational analytic research design. The total samples were 158 patients, according to inclusion and exclusion criteria. The sampling technique used purposive sampling. Data analysis used chi square test. Results: The results 158 patients, divided into 79 (50%) patients with BV and 79 (50%) patients without BV. Based on BMI, 88 (55.7%) patients with normal BMI and 70 (44.3%) people with abnormal BMI. Patients with normal BMI were mostly not BV, that was 56 (63.6%) people and 32 (36.4%) people were BV positive. Patients with abnormal BMI were mostly BV, that was 47 (67.1%) people and 23 (32.9%) people did not BV. Statistical analysis showed there was a significant association between the incidence of bacterial vaginosis with body mass index (p= 0.001) with contingency coefficient 0.292. Conclusion: There is associated between the incidence of bacterial vaginosis with body mass index in RSUD Dr. Soetomo in 2017-2018.